(untitled) (African Journal of Public Administration & Management, 2026)
Fresh graduates are usually unable to transition smoothly into employment due to employers’ high expectations for abilities and personal qualities (Helyer and Lee, 2014). Sub-Saharan Africa needs 25 million new jobs annually (World Bank, 2025). Malawi’s youth unemployment rate is at 23%. The Ministry of Labour in Malawi has been implementing the Graduate Internship Programme (GIP) since 2018, reaching 20232 graduates (11 cohorts) with the to provide work-integrated experience to improve their employability